2017
DOI: 10.1097/adm.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine Increases the Likelihood That Abstinence Can Withstand Unstructured Time in Buprenorphine-maintained Outpatients

Abstract: Objective In a clinical trial examining daily clonidine as an adjunct to buprenorphine treatment for opioid dependence, we found that clonidine increased opioid abstinence and decoupled stress from craving. From a personalized-medicine perspective, the next step is to identify people for whom clonidine would be beneficial. To that end, using data from the same clinical trial, we examined the associations of daily-life activities with treatment success. Methods Outpatients (N=118) received clonidine (0.3 mg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Continuous 7-day treatment with the α 2 adrenergic agonist clonidine was selected as an active negative control. Clonidine will relieve some somatic opioid withdrawal signs in opioid-dependent OUD patients and has been shown to decrease stress-induced reinstatement in rats as well as reduce the risk of relapse when used as an adjunct to buprenorphine in humans [23][24][25]. However, clonidine does not prevent relapse when used as a monotherapy [26].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous 7-day treatment with the α 2 adrenergic agonist clonidine was selected as an active negative control. Clonidine will relieve some somatic opioid withdrawal signs in opioid-dependent OUD patients and has been shown to decrease stress-induced reinstatement in rats as well as reduce the risk of relapse when used as an adjunct to buprenorphine in humans [23][24][25]. However, clonidine does not prevent relapse when used as a monotherapy [26].…”
Section: Introductionmentioning
confidence: 99%
“…This controlled trial concerning the use of clonidine as an adjunct to buprenorphine, provided participants with a portable device that would prompt them at four random intervals a day to record their current level of craving and any activities they were engaging in presently. The authors found that engaging in responsibilities is related to positive treatment outcomes in individuals receiving standard opioid agonist therapy [ 32 ]. Although our study was qualitative, it complements the literature suggesting that good treatment outcomes arise from commitments and responsibilities [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The D&A program appeared to provide a novel forum where men were able to discuss their internal emotional state. The prison population has a high prevalence of emotional burden [ 32 ]. This is contributed to by the situation inmates are in and the difficult life circumstances leading to incarceration.…”
Section: Discussionmentioning
confidence: 99%